Analisis Faktor - Faktor Yang Mempengaruhi Preferensi Konsumen Dalam Pembelian Produk Frozen Food (Studi Kasus Pelanggan “Nadelia Frozen” Patumbak Medan) - Rivaldi Pranata; Rahmayati Rahmayati (Journal of Islamic Economics and Finance, 2023)
Frozen food is food that is processed and then packaged in half-cooked packaging and when consumed must go through a re-processing process, namely by heating it in a frying pan. Frozen Food is a storage process before processing. Frozen food or processed frozen food is the result of a food preservation method which is carried out by lowering the temperature to freezing point, this aims to slow down the spoilage process and preserve the food for months depending on the type of food. Frozen food is also defined as food that is frozen with the aim of preserving the food until it is ready to be eaten. This research design uses quantitative research methods, which test certain theories by examining the relationships between variables. These variables are measured using research instruments, so that data consisting of numbers can be analyzed based on statistical procedures. This type of research uses associative research. Associative research is a temporary answer to associative problem formulations, namely those that ask about the relationship between two or more variables. In this research, we analyze the influence of price and promotion on consumer preferences at the "Nadelia Frozen" shop in Patumbak Medan. Based on data obtained in research regarding Analysis of Factors that Influence Product Purchases. The number of respondents in this study was 30 respondents, then analyzed, it was concluded as follows: Based on partial research results, the brand variable is the most dominant factor that has a positive and significant influence on purchasing frozen food products. Based on partial research results, the product variable has a positive and significant effect. on purchasing frozen food products, based on partial research results, the market competition variable has no effect on purchasing frozen food products. Based on simultaneous research results, the variables Brand, Product and Market Competition have a positive and significant effect on purchasing frozen food products. Based on the conclusions, suggestions that can be put forward in increasing purchases of frozen food products in Patumbak Medan are: Considering that brands and products have a positive and significant influence on purchases of frozen food products in Patumbak Medan, it is best to maintain and improve product quality and maintain the good name of the brand. It is hoped that the company will make strategies for building brand images, products so they can compete in the market. The results of this research can be used to develop management knowledge in the future to be better at marketing products with known brands, so they can compete in market competition.